From threat perception to use hesitancy: examining college students’ psychological barriers to generative AI adoption - Yin, Yukun (Frontiers in Education, 2025)
The usefulness and ease of use of generative artificial intelligence (GAI) technology serve as the necessary technical foundation for its rapid proliferation. However, within the current educational landscape, students have raised growing concerns and apprehensions regarding the ethical governance of GAI technologies and their potential to disrupt employment opportunities through job displacement effects. This study investigated the relationship between perceptions of threats and hesitancy concerning the use of GAI technology among college students. A survey of 805 participants revealed a positive correlation between perceived technological threat and use hesitancy. Importantly, perceived avoidability and fear of GAI were found to serve as sequential mediators in this relationship. These findings elucidate the psychological mechanisms that underlie students’ reluctance to adopt emerging GAI technologies and suggest that interventions aimed at addressing threat perceptions, increasing avoidability, and reducing fear may promote greater acceptance of such techniques among students.